A review of computational thinking interventions in upper elementary education - María Eugenia Curi; Anaclara Gerosa; Marcos Viera; Alejandra Carboni (Computers and Education Open)
This review examines current trends in Computational Thinking (CT) educational interventions. Analyzing 54 studies from 2012 to 2024, the review identifies key trends in the implementation of CT interventions, including duration, number of participants, and programming tools. Most interventions with upper-elementary students span more than a month, involve between 20 and 100 children, and use unplugged activities and visual programming environments. The review also investigates the extent to which student context data, such as gender and socioeconomic background, are considered, highlighting the importance of these factors in CT interventions. The findings suggest that while some interventions account for gender and contextual differences, there is a potential for a greater focus on these aspects to address social inequalities. This study provides valuable insights into the potential impact and inclusiveness of CT educational strategies, serving as a resource for educators, researchers, and policy makers aiming to improve CT integration into educational frameworks.